Exploring elderly patients' experiences of recovery following complex proximal humerus fracture: A qualitative study. - Sabharwal,S; Archer,S; Cadoux-Hudson,D; Griffiths,D; Gupte,CM; Reilly,P (J Health Psychol, 2019)
This study explores the experiences and perceptions of recovery in elderly patients who had sustained a proximal humerus fracture. In-depth semi-structured interviews were conducted with 15 patients over the age of 65. Thematic analysis identified aspects of care that impacted upon patient experience and quality of life. Seven main patient-reported themes were identified, including pain, sleep, shoulder function, emotional state, social support, relationship with their professional and experience of healthcare institution. These themes offer insight into the experiences of adults receiving care for proximal humerus fracture and highlight that existing quantitative measures of quality of life do not measure domains that are important to patients.